Practice of Magnetrezeki - lowering the line of truth to build critical thinking, social leadership so that good communication is built - Khairia; Hasiolan Nasushan; Anna Navita (Journal of Islamic, Social, Economics and Development, 2024)
This research aims to explore the application of Magnetrezeki, a spiritual and practical approach in self-development, with a focus on the aspect of lowering the line of truth (ego) to build critical thinking, strong social leadership, and effective communication. This study uses a qualitative method, by conducting observations both inside and outside the graduate class through discussions and interviews, visual analysis, literature studies, and interviews (individual or group). The results of the study show that by lowering the ego or line of truth, individuals can increase openness in critical thinking, be better prepared to accept different views, and be able to overcome personal biases. This has an impact on leaders' ability to build more inclusive and collaborative social leadership. In the context of social leadership, lowering the ego creates an environment that is more conducive to effective communication, where each member of the group feels valued and actively contributes. Thus, lowering the line of truth has an effect on critical thinking, social leadership, and effective communication skills, especially in social and organizational contexts. It starts with improving the quantum world.